Common law households and marriage frequency 1974 - Trost, Jan (Uppsala University, 2026)
The aim is that the material should illustrate the unmarried cohabitation that has been more frequent from the mid-sixties. Married couples are compared with unmarried cohabitant couples from Gävle. Questions about personal data, background to cohabitation and/or marriage, engagement and marriage, parents and knowledge about legal and social matters.

Syftet är att materialet ska illustrera det ogifta samboförhållandet som har blivit vanligare sedan mitten av 1960-talet. Gifta par jämförs med ogifta sambopar från Gävle. Frågor rör personuppgifter, bakgrund till samboförhållande och/eller äktenskap, förlovning och giftermål, föräldrar samt kunskap om juridiska och sociala frågor.
Ogift samboende och äktenskapsfrekvens 1974
Keywords: Marriage rate; Äktenskapsfrekvens; Legislation and legal systems; Lagstiftning och rättssystem; Family life and marriage; Familjeliv och äktenskap; Social Sciences; Samhällsvetenskap